Influência da quimioterapia na expressão de citocinas pró-inflamatórias tecidual na periodontite experimental - Cunha, Clara Possarle [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This study comparatively evaluated the influence of the chemotherapeutic agent Cisplatin (CIS), both over the healthy periodontium and the progression of experimental periodontitis (EP), as well as kidney functions of the rats with EP under chemotherapy. Materials and Methods: 120 male rats were distributed in 4 groups (n=30). NEP-SS group: animals that received injections of 0,5ml of 0,9% saline solution (SS) without EP induction (Sham group). EP-SS group: animals that received injections of 0,5 ml of SS and induction of EP after de first injection. NEP-CIS group: animals that received CIS injections without EP induction. EP-CIS group: animals that received CIS injections and PE induction after the first injection. For EP induction a cotton thread number 24 was fitted around the first left lower first molar. After 07, 15 and 30 days after the first intraperitoneal injection (SS or CIS), animals were euthanized. The collected mandibles were submitted to immunohistochemical analysis in the furcation region of the first lower molar for evaluation of the biomarkers TNFα and IL1β. Blood samples were collected for biochemical analyzes of creatinine and urea, before injections and at 07 and 30 days. Data were submitted to statistical analysis (p<0,05). Results: EP-CIS showed greater intensity and extension of the inflammatory response, and decreased repair process compared with group EP at all experimental periods. EP-CIS had significantly increased levels of urea and showed no significant difference in creatinine' levels. Conclusion: CIS influenced the increased expression of proinflammatory cytokines in healthy periodontal tissues, as well ass, in presence of EP, exacerbated the inflammatory process in the furcation region. Additionally, EP increased serum levels of urea, indicating an intensification of the renal damages caused by CIS

Este estudo avaliou comparativamente a influência do quimioterápico Cisplatina (CIS), no periodonto saudável e sobre a evolução da periodontite experimental (PE), bem como a função renal de ratos portadores de PE submetidos ao tratamento com o quimioterápico. Materiais e Métodos: 120 ratos machos, foram distribuídos em 4 grupos (n=30). Grupo SPE-SS: animais que receberam injeções de 0,5 ml de solução salina 0,9% (SS) sem indução da PE (grupo sham). Grupo PE-SS: animais que receberam duas injeções de 0,5 ml de SS e indução da PE após a primeira injeção. Grupo SPE-CIS: Animais que receberam injeções de CIS sem indução da PE. Grupo PE-CIS: Animais que receberam injeções de CIS e indução da PE após a primeira injeção. Para indução da PE foi adaptado um fio de algodão 24 ao redor do primeiro molar inferior esquerdo, logo após a primeira dose da medicação. Decorridos 07, 15 e 30 dias após a primeira injeção intraperitoneal (SS ou CIS) os animais foram eutanasiados. As mandíbulas coletadas foram submetidas à análise imunoistoquímica na região de furca do primeiro molar inferior onde foram avaliados os biomarcadores: TNFα e IL1β. Foi realizada a coleta sanguínea para análise bioquímica de Creatinina e Ureia previamente às injeções, e aos 7 e 30 dias. Os dados obtidos foram submetidos a análise estatística (p<0,05). Resultados: Observou que o grupo PE-CIS apresentou maior intensidade da resposta inflamatória em todos os períodos e menor processo de reparo frente a PE. O grupo PE-CIS apresentou de maneira significante maiores níveis de ureia nos períodos iniciais e não apresentou diferença significativa nos níveis de creatinina. Conclusão: A CIS influenciou o aumento na expressão de citocinas pró-inflamatórias nos tecidos periodontais saudáveis, além de, na presença da PE, ter exacerbado...
Keywords: Periodontite; Quimioterapia; Modelos animais; Periodontitis